Shelf-life enhancement of papaya with aloe vera gel coating at ambient temperature (Journal of the Bangladesh Agricultural University, 2016)
In this experiment the effects of aloe vera gel coating on storage behavior of papaya at room temperature (290C-310C) was studied. Physico-chemical parameters such as color, physical changes, moisture, ash, acidity, vitamin C, protein, fat and total soluble solids (TSS) of papaya and aloe vera was determined at 3 days interval during the storage period. Among the physico-chemical parameters, color, physical changes, total weight loss and TSS contents increased significantly, whereas moisture content, vitamin C and titrable acidity decreased during storage. Control and 0.5% aloe vera treated papaya decayed from 6 days onward and completely decayed within 12 days of storage. On the other hand, 1% and 1.5% aloe vera gel coated papaya maintained their shelf-life for 9 and 12 days, respectively. Some of 1.5% aloe vera coated papaya decayed after 15 days. Papaya treated with 1.5% aloe vera solution, maintained their color & physical changes compared to other treatments up to 12 days of storage. The overall results showed the superiority of 1.5% aloe vera gel coating in extending the shelf-life of papaya upto 15 days compared to that of 0.5%, 1% aloe vera gel coating and control papaya. The present study describes the preparation and potential application of aloe vera gel coatings for enhancing the postharvest life and quality of papaya.J. Bangladesh Agril. Univ. 13(1): 131-136, June 2015